SEMICONDUCTORS: THE HISTORY OF FORMATION AS A SCIENCE. DEFECTS IN THE CRYSTAL STRUCTURE. ELECTRICAL CONDUCTIVITY AND CONTACT PHENOMENA - Kuchkorov Mavzurjon Khursanbayevich; Mukhammadyusupova Mokhinur Vohidjon kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article mainly covers basic information about semiconductors, the history of the formation of semiconductor physics, crystal structure defects, their electrical conductivity, contact phenomena, semiconductor devices and research in this area, problems and shortcomings, as well as achievements. It is also reported that solar cells based on the internal photoelectric effect are called light-emitting diodes, and solar cells-semiconductor silicon solar cells that convert solar energy into electrical energy-are called solar cells. Again with the aim of developing the field of semiconductors Information about the strengthening of the activities of the Institute of Semiconductor Physics at the National University, that currently semiconductors occupy an important place in science and technology, as well as that semiconductor electronic devices are used in various sectors of the national economy is highlighted.